COMPARATIVE EVALUATION OF MATRICING TECHNIQUES USED IN CLASS II AMALGAM RESTORATIONS -A RETROSPECTIVE STUDY - UB, Swathi; Ramesh, Sindhu; Priscilla Antony, Delphine (International Journal of Psychosocial Rehabilitation, 2020)
In class II amalgam restorations, the matrix band serves as a missing wall in such preparations to contain the amalgam during condensation, restoring form to the restoration. In dentistry, the matrix band plays an important role in restoring interproximal surfaces of the tooth. The purpose of this study was to evaluate the various types of matrices that were used for reconstructing the proximal contact area in class II amalgam restorations.For this retrospective study, data was taken from the patient records collected from Saveetha Dental College Chennai. Data collected consisted of 853 cases of Class II Amalgam restorations, in which the type of matricing technique was evaluated over a period of one year from 10th June 2019 to 1st March 2020. The chi square test was used for statistical analysis. In this study, the type of matricing technique used in class II Amalgam restorations was evaluated based on the patient's age, gender, procedure, and tooth in which the restoration was done. Results of the study were not found to be statistically significant. (P value > 0.5). The tofflemire metricing technique was the most preferred technique of metricing for Class II amalgam restorations (38%), followed by sectional matrix (35%), ivory number 1 (19.3%), and ivory number 8 (8.1%). The Tofflemire matrices technique was the most commonly preferred technique for restoring proximal contacts of class II amalgam restorations. A Tofflemire-type retainer helps to lock the tooth securely, can be released instantly, and is easily adjustable.